Uterine Preservation Treatments in Sarcomas: Oncological Problems and Reproductive Results: A Systematic Review - Giulia Dondi (MDPI AG, 2021)
Uterine sarcomas are rare cancers, sometimes diagnosed in women of childbearing age. Hysterectomy is the standard treatment in early stages. The option of lesion removal to save fertility is described in the literature, but it is still considered experimental. The objective of this systematic review is to report on the available evidence on the reproductive and oncological outcomes of fertility-sparing treatment in women with uterine sarcomas. PubMed, Scopus and Cochrane Central Register of Controlled Trials were searched between 1 January 2011 and 21 June 2021 for publications in English about women with uterine sarcoma treated with a fertility-sparing intervention. Thirty-seven studies were included for a total of 210 patients: 63 low-grade endometrial stromal sarcomas, 35 embryonal rhabdomyosarcomas of the cervix, 19 adenosarcomas, 7 leiomyosarcomas and 2 uterine tumors resembling an ovarian sex cord. Conservative treatment ensured pregnancy in 32% of cases. In terms of oncological outcomes, relapse was related to histology and the worst prognosis was reported for leiomyosarcoma, followed by low-grade endometrial stromal sarcoma, which relapsed in 71% and 54% of cases, respectively. The highest death rate was associated with leiomyosarcoma (57.1%). This study demonstrated that fertility-sparing treatments may be employed in selected cases of early stage uterine sarcoma.